A RELEVÂNCIA DA EDUCAÇÃO FINANCEIRA NA FORMAÇÃO DE JOVENS - Cazella, Carla; De Brito , Thainara (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2021)
This article presents an analysis of financial education and its insertion in the lives of young people, citing the view of some experts on the subject and the experience of academics in this environment. Objective: Identify an importance of Education and economics in Financial Education, understanding the perception and Academic experiences of Unoesc Chapecó-SC and understanding the understanding of perception of financial market professionals regarding the importance of Financial education for young people. Method: Research was carried out through form with 40 questions by google forms for academics of university and insert the results found in this process through the percentage of each answer. The research included 41 academics, carried out during an online meeting with University professors about the financial education with the aim of developing this practice in the environment family and take the information to the community. As results we conclude that Financial education broadens your understanding respect for these choices. Through projects and events prepared by UNOESC these experiences have been spreading and bringing transformations to the academics and society.